2020
DOI: 10.18196/agr.6187
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Determinants of Farmer’s Participation in Sugarcane Contract Farming in Indonesia

Abstract: The integrated value chain is a prerequisite for the successful industrialization of the agricultural sector. Contract farming (CF) is a useful instrument to integrate the agricultural value chain in developing countries such as Indonesia. The purpose of this study was to identify the determinants of farmer participation in sugarcane contract farming. The data utilized in this study was obtained from the Indonesian Plantation Farm Household Survey 2014 for Sugarcane. The data consists of 8.831 farmers distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
1
7
0
1
Order By: Relevance
“…Therefore, it can be concluded that the availability of more land encourages farmers to implement the Jajar Legowo system in rice farming. This is consistent with previous studies by [22] and [23] which discovered that land area had a positive and significant effect on farmers' decision-making. The odds ratio value of the land area of 19,166 means that farmers with large land had a higher chance of applying the Jajar Legowo system 19,166 times greater than to farmers with narrow land.…”
Section: Factors Influencing Farmers' Decision To Implement the Jajar Legowo Planting Systemsupporting
confidence: 93%
“…Therefore, it can be concluded that the availability of more land encourages farmers to implement the Jajar Legowo system in rice farming. This is consistent with previous studies by [22] and [23] which discovered that land area had a positive and significant effect on farmers' decision-making. The odds ratio value of the land area of 19,166 means that farmers with large land had a higher chance of applying the Jajar Legowo system 19,166 times greater than to farmers with narrow land.…”
Section: Factors Influencing Farmers' Decision To Implement the Jajar Legowo Planting Systemsupporting
confidence: 93%
“…The second stage was the selection of plantation farm households. The eligible farm households were those with a cropping area of at least 650 m 2 (Rokhani et al, 2020). Table 2 presents the descriptive statistics of the data.…”
Section: Methodsmentioning
confidence: 99%
“…In general, education plays a crucial role in farm decisions making in Indonesia. Farmer's education significantly affects participation in contract farming for tobacco [33], sugarcane [34], and broiler farmers [35,36]. Furthermore, education also significantly affects the adoption of certified seed plants for Indonesian sugarcane farmers [37].…”
Section: Educationmentioning
confidence: 99%
“…Land tenure security also plays a crucial role in Indonesian agriculture. Land tenure security increases the productivity and profitability of rice farming in Indonesia [41], the probability of participating in contract farming [34], and the adoption of certified seed plants [37]. A weak land tenure security lessens farm investment and makes the farmer more vulnerable to shocks, including climate change.…”
Section: Land Tenurementioning
confidence: 99%